A Fault-Tolerant Detection Fusion Strategy for Distributed Multisensor Systems. (11th February 2016) - Zhao, Shengli; Zhou, Jie
Abstract : The distributed detection fusion formulation (DDFF) in ideal multisensor systems has been studied over the last two decades. If some local sensors cannot work normally, the detection performance of system may reduce significantly. It is meaningful to design fault-tolerant detection fusion rules which can guarantee the performance of system no matter whether the fusion center and local sensors work well or not. A new distributed detection fusion strategy is thus proposed by minimizing a weighted sum of risk at the fusion center and risks at the local sensors, and then a fault-tolerant distributed detection fusion formulation (FT-DDFF) is derived. Some numerical examples illustrate the performance of the proposed formulation. If the whole system is perfect, compared with the DDFF, the FT-DDFF has both small risks of local sensors and a little small risk of fusion center with an appropriately selected parameter. While some local sensors cannot work, the FT-DDFF would perform better than the DDFF at fusion center in average.